KEPASTIAN HUKUM PEMBIAYAAN DALAM UPAYA PENEMPATAN PEKERJA MIGRAN INDONESIA DI LUAR NEGERI - Herdiman, Heru; Maryano, Maryano; Hakim, Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Financing the placement of Indonesian Migrant Workers (PMI) abroad still faces the problem of unclear schemes, cost transparency, and potential losses for PMI. The existence of legal certainty in financing that is fair, transparent, and guarantees the protection of PMI rights in accordance with laws and regulations. The legal norm has not been fully implemented consistently in the field, so a study is needed on the legal certainty of financing in order to realize the placement of PMI that is fair and protected. The method used in this study is normative legal research conducted as an effort to obtain the necessary data in connection with the problem. Data used with secondary data and tertiary legal materials. In addition, primary data is also used as supporting secondary data legal materials. For data analysts conducted by the method of qualitative juridical analysis. The results of the study that the arrangement of financing the placement of Indonesian Migrant Workers (PMI) has actually been regulated comprehensively in law No. 18 of 2017 and its Implementing Regulations, but the legal certainty is not optimal due to regulatory inconsistency, weak implementation of cost transparency, and ineffective implementation of zero cost policy and the principle of Employer Pays, especially in destination countries such as Saudi Arabia, Malaysia, and Singapore. Therefore, it is necessary to strengthen legal certainty through harmonization and codification of financing regulations, affirmation of transparent and binding Employer Pays principles, integrated digital supervision, and strengthening law enforcement through cross-agency coordination such as BP2MI, the Ministry of manpower, the Indonesian National Police, the Attorney General's Office of the Republic of Indonesia, and the Financial Services Authority